2014
DOI: 10.1007/s10597-014-9788-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Cost-Savings Threshold for HIV Adherence Intervention Studies for Persons with Serious Mental Illness and HIV

Abstract: Persons with serious mental illnesses are at increased risk for contracting and transmitting HIV and often have poor adherence to medication regimens. Determining the economic feasibility of different HIV adherence interventions among individuals with HIV and serious mental illness is important for program planners who must make resource allocation decisions. The goal of this study was to provide a methodology to estimate potential cost savings from an HIV medication adherence intervention program for a new st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We selected the cost-savings threshold method as we believed this model-building construct was suited to address within-procedure variation and ultimately serve as another avenue for evaluating the economic impact of orthopaedic technologies. 14,38 In addition, while the notion of a cost-savings threshold is not universally known in orthopaedics, we believe it to be intuitive to understand and pragmatic as a simple concept that surgeons, administrators, payers, and patients can share a dialogue around. With the above accounting and analysis plan, we used 2-way sensitivity analysis to derive a generalizable roadmap for other institutions to evaluate their own cost-savings threshold for PSI in TAR and other orthopaedic procedures (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We selected the cost-savings threshold method as we believed this model-building construct was suited to address within-procedure variation and ultimately serve as another avenue for evaluating the economic impact of orthopaedic technologies. 14,38 In addition, while the notion of a cost-savings threshold is not universally known in orthopaedics, we believe it to be intuitive to understand and pragmatic as a simple concept that surgeons, administrators, payers, and patients can share a dialogue around. With the above accounting and analysis plan, we used 2-way sensitivity analysis to derive a generalizable roadmap for other institutions to evaluate their own cost-savings threshold for PSI in TAR and other orthopaedic procedures (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…For cost analysis, we borrowed the concept of a “cost-savings threshold”—an analysis method applied in the public health sciences to determine the acceptable price of an intervention. 38 The cost-savings threshold is the price point for an intervention below which net cost savings are realized for the buyer. We selected the cost-savings threshold method as we believed this model-building construct was suited to address within-procedure variation and ultimately serve as another avenue for evaluating the economic impact of orthopaedic technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PATH+ intervention found that patient navigators, like advanced practice nurses, are a cost-effective method of improving outcomes for individuals with comorbid HIV and SMI [49, 51]. International research has shown a similar need for integrated care, given the high burden of co-occurring HIV and SMI in some resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving retention and adherence to ART medication [50], the intervention also significantly reduced viral load and improved mental quality of life compared to the control group [49]. Wu and colleagues conducted a cost analysis of this intervention using CD4 cell count improvements as a measure of benefit [51]. Among the intervention group, participants whose baseline CD4 count was ≤50 cells/mL saw the most benefit, with an average increase of 264 cells/mL over the 12 month intervention period.…”
Section: Secondary Hiv Preventionmentioning
confidence: 99%